41. Age effect on intraoperative motor evoked potentials in children. Issue 1 (January 2015) - Costa, P.; Giobbe, M.L.
<x xml:space="preserve">Abstract</x> Although intraoperative Motor Evoked Potentials (MEPs) are routinely used in pediatric population in order to prevent jatrogenic neurologic sequelae, studies on the effect of age on m-MEPs in children are still sparse. In this retrospective study, data from 116 procedures in 102 children (mean age 8.1 ± 4.5 yrs undergoing neurosurgical or orthopedic procedures (37 spinal – 31.9% –, 68 posterior fossa – 55.6% – and 11 supratentorial – 9.52% –) are shown. We reviewed the stimulus intensity (expressed as stimulator output percentage) required to achieve a robust MEP from the aductor pollicis brevis (ABP). It has been possible to obtain responses from the ABP in all subjects. An inverse correlation between increasing age and stimulus intensity has been found in the first decade of life (R −0.437; p < 0.01). Young children (<5 yrs) required stronger stimulus intensity (43.9% ± 15.9) compared to patients > of 5 yrs (31.6% ± 10.9; t 4.432; p < 0.001). No patient experienced any transcranial electrical stimulation complications. This study confirm the feasibility of MEPs even in young children and the association between age and MEPs threshold. High stimulation intensities needed to produce MEP responses in younger patients may reflect immaturity of their motor pathways.